Pathological Conditions Associated with the Male Reproductive Tract of the Sahel Bucks. (24th March 2014) - Abba, Yusuf; Simon, Suleiman; Idris Gambo, Halima; Onyebuchi Igbokwe, Ikechukwu; Iliyasu, Yusuf
Abstract : The study of pathological conditions of the male reproductive system is paramount to understanding reproductive inefficiency in the Sahel goat. In this study, 1048 Sahel bucks presented for slaughter at the Maiduguri metropolitan abattoir were evaluated for the presence of various pathological abnormalities of the reproductive system. A total incidence of 15.08% was recorded for various pathological conditions, with testicular, penile, and scrotal conditions having incidences of 7.82%, 4.80 and 2.50%, respectively. Bilateral testicular hypoplasia and atrophy and unilateral cryptorchidism accounted for incidences of 4.10%, 2.38%, and 1.24%, respectively, while paraphimosis and scrotal laceration had incidences of 1.72% and 1.05%, respectively. Age specific incidence of pathological conditions were not significant ( P > 0.05 ) between bucks aged <1–1.5 and 2–2.5 years. However, bucks aged 3–3.5 year a had lower ( P < 0.05 ) incidence of pathological conditions than other age groups. Histopathological evidence of inflammation, degeneration, and atrophy was observed in the testes, while inflammatory changes were observed in the prepuce.